2019
DOI: 10.1186/s12937-019-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of 8 to 10 years old children within 20 years following compulsory salt iodization policy in Shanghai, China

Abstract: Background: In 1996, Shanghai implemented universal salt iodization and has became the last provincial unit in China to carry out this intervention. In this study, we summarized achievements in past 20 years, to provide suggestions and evidence for the next stage of iodine supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
(18 reference statements)
3
16
0
Order By: Relevance
“…In addition, for inland children who consumed either iodized salt or non-iodized salt, the median UIC steadily remained between 100 and 199 μg/L. This finding indicates that school-age children remains iodine-sufficient even when they did not use iodized salt at home, which is in line with the study conducted in Shanghai [32]. It is presumed that the major dietary source of iodine may not be from home-salt-prepared foods, but other commercial foods prepared with iodized salt, e.g.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, for inland children who consumed either iodized salt or non-iodized salt, the median UIC steadily remained between 100 and 199 μg/L. This finding indicates that school-age children remains iodine-sufficient even when they did not use iodized salt at home, which is in line with the study conducted in Shanghai [32]. It is presumed that the major dietary source of iodine may not be from home-salt-prepared foods, but other commercial foods prepared with iodized salt, e.g.…”
Section: Discussionsupporting
confidence: 85%
“…However, the current standard during pregnancy recommended by WHO/ UNICEF/ICCIDD is based on non-pregnant populations: this might lead to overestimation of iodine deficiency during gestation, so the lower limit may be too high (24) . Monitoring by the Shanghai CDC showed that the median UIC in children aged 8-10 years was >100 μg/l after the implementation of the USI policy, indicating that children aged 8-10 years have sufficient iodine intake (12) . Since the median UIC from a representative child's spot urine sample can be used to classify the iodine status of a population (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring data in Shanghai showed that the percentage of households choosing iodised salt dropped from 94•6 % in 1999 to 76•5 % in 2017 (12) . In theory, with more families opting for non-iodised salt, the median UIC in the population should be on a downwards trend.…”
mentioning
confidence: 99%
“…Shanghai has followed the national compulsive universal salt iodization (USI) policy since 1996; the city began monitoring the iodine status of children 8-10-year old in 1995 and of pregnant women in 2009. According to the monitoring data, the iodine status of Shanghai's 8-10-year-old children has been adequate since 2005, but the MUIC of pregnant women has indicated mild iodine de ciency, with a level of only 135.9 µg/L in 2009, 139.8 µg/L in 2012, and 126.5 µg/L in 2015 [14][15][16]. Furthermore, monitoring in Shanghai has revealed that more and more families choose non-iodized salt as their cooking salt, and the rate of households with iodized salt dropped from 94.6% in 1999 to 76.5% in 2017 [16].…”
Section: Introductionmentioning
confidence: 99%
“…According to the monitoring data, the iodine status of Shanghai’s 8–10‐year‐old children was adequate after 2005, although the MUIC of pregnant women has indicated mild iodine deficiency, with a level of only 135.9 μg L −1 in 2009, 139.8 μg L −1 in 2012 and 126.5 μg L −1 in 2015 ( 13–15 ) . Furthermore, monitoring in Shanghai has revealed that more and more families choose non‐iodised salt as their cooking salt, and the rate of household using iodised salt has dropped from 94.6% in 1999 to 76.5% in 2017 ( 15 ) . Hence, the iodine level in pregnant women has become a concern.…”
Section: Introductionmentioning
confidence: 99%